PERAN AYAH TERHADAP KECENDERUNGAN PERILAKU BULLYING - Dina, Jaysika Hafidz (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research is driven by the increasing phenomenon of bullying behavior among adolescents and the importance of fathers' roles in building children's behavior. The purpose of this study is to determine the relationship between fathers' roles and the tendency to engage in bullying behavior among adolescents in Sungailiat. The research method employed was quantitative with a descriptive correlational design. The number of respondents was 69 adolescents selected through purposive sampling using the Lemeshow formula. The research instrument was a questionnaire distributed online using Google Forms. Data analysis was conducted using descriptive and bivariate analysis. The results show that the higher the father's role, the lower the tendency to engage in bullying behavior among adolescents. There was a strong and significant positive relationship between fathers' role and control over bullying behavior (r = 0.638; p < 0.05). All respondents had a very positive perception of their fathers' role and high levels of control over bullying behavior. Therefore, it can be concluded that an optimal father's role is closely related to a child's low tendency to engage in bullying